Numerical investigation of membrane oxygenation using sub-channel analysis. Issue 12 (3rd December 2018) - Subraveti, Sai Nikhil; Vinod Kumar, V.; Pothukuchi, Harish; Sai, P.S.T.; Patnaik, B.S.V.
Abstract : Purpose: Better membrane oxygenators need to be developed to enable efficient gas exchange between venous blood and air. Design/methodology/approach: Optimal design and analysis of such devices are achieved through mathematical modeling tools such as computational fluid dynamics (CFD). In this study, a control volume-based one-dimensional (1D) sub-channel analysis code is developed to analyze the gas exchange between the hollow fiber bundle and the venous blood. DIANA computer code, which is popular with the thermal hydraulic analysis of sub-channels in nuclear reactors, was suitably modified to solve the conservation equations for the blood oxygenators. The gas exchange between the tube-side fluid and the shell-side venous blood is modeled by solving mass, momentum and species conservation equations. Findings: Simulations using sub-channel analysis are performed for the first time. As the DIANA-based approach is well known in rod bundle heat transfer, it is applied to membrane oxygenators. After detailed validations, the artificial membrane oxygenator is analyzed for different bundle sizes (L/W) and bundle porosity (epsilon) values, and oxygen saturation levels are predicted along the bundle. The present sub-channel analysis is found to be reasonably accurate and computationally efficient when compared to conventional CFD calculations. Research limitations/implications: This approach is promising and has far-reaching ramifications to connect and extend a well-known rod bundle heat transfer algorithm to a membrane oxygenator community. As a variety of devices need to be analyzed, simplified approaches will be attractive. Although the 1D nature of the simulations facilitates handling complexity, it cannot easily compete with expensive and detailed CFD calculations. Practical implications: This work has high practical value and impacts the design community directly. Detailed numerical simulations can be validated and benchmarked for future membrane oxygenator designs. Social implications: Future membrane oxygenators can be designed and analyzed easily and efficiently. Originality/value: The DIANA algorithm is popularly used in sub-channel analysis codes in rod bundle heat transfer. This efficient approach is being implemented into membrane oxygenator community for the first time.